Distribution of Haemagogus and Sabethes (Diptera: Culicidae) populations in relation to forest cover and climatic factors in the Chapada dos Guimarães National Park, State of Mato Grosso, Brazil - Alencar, Jeronimo (2018)
Members of the genera Haemagogus and Sabethes are the most important biological vectors of the wild yellow fever virus (WYF) in the forested areas of the Americas. The ecologies of Haemagogus janthinomys, Hg. leucocelaenus, Sabethes chloropterus, and Sa. glaucodaemon were studied in a forest of the Chapada dos Guimarães National Park, state of Mato Grosso, Brazil, to evaluate the influence of climatic factors (temperature and relative humidity [RH]) on their abundance. We also examined the association of climate with landscape structure on species distribution patterns throughout the seasons of the year. Multiple stepwise regressions showed that RH was most likely to influence the density of mosquito populations. A multidimensional scaling (MDS) was used to evaluate the effects of forest cover on the composition of mosquito populations at different radii (100-, 250-, and 1,000-m-radius buffer areas). The MDS provided 2 dimensions with values that indicated a higher similarity in the composition of culicid populations between sites 1 and 3, while site 2 was separate from the others in the ordination space. Site 2 had a much higher forest cover ratio at 100-m radius compared with sites 1 and 3. We found a possible relationship between the forest cover and the composition of the mosquito populations only in the 100-m radius. These results enabled us to infer that RH directly favored the activity of mosquito populations and that the forest cover located closest to the sampling site may influence the species composition. Since mosquito abundance was higher in the sites with lower local forest cover, forest fragmentation may be a key factor on the presence of WYF vector.